Salts of 5‐(5‐Azido‐1H‐1, 2, 4‐triazol‐3‐yl)tetrazol‐1‐ol: From Highly Sensitive Primary Explosives to Insensitive Nitrogen‐Rich Salts. Issue 32 (20th September 2013) - Izsák, Dániel; Klapötke, Thomas M.; Reuter, Stephan
Abstract: Several metal and nitrogen‐rich salts of the recently presented 5‐(5‐azido‐1 H ‐1, 2, 4‐triazol‐3‐yl)tetrazol‐1‐ol (AzTTO), including silver (1 ), copper(I) (2 ), potassium (3 and5 ), cesium (4 ), copper(II) (6 ), ammonium (7 and11 ), hydrazinium (8 ), guanidinium (9 and12 ), and aminoguanidinium (10 ), were prepared and thoroughly characterized by IR and multinuclear ( 1 H, 13 C, 14 N) NMR spectroscopy, mass spectrometry, and differential scanning calorimetry (DSC). Additionally, the structures of3· H2 O, 4, 5· 3H2 O, and7 were determined by single‐crystal X‐ray diffraction. The compounds show interesting structural motifs, which were analyzed and are discussed. The sensitivities towards impact, friction, and electrostatic discharge were determined according to BAM (the German Federal Institute for Materials Research and Testing) standards, thereby revealing most of the metal salts to be highly sensitive and the nitrogen‐rich salts to be mostly insensitive. Furthermore, the metal salts were tested for their ability to be primary explosives. Abstract : The reaction of the recently presented 5‐(5‐azido‐1 H ‐1, 2, 4‐triazol‐3‐yl)tetrazol‐1‐ol (AzTTO) with various metal and nitrogen‐rich bases leads to several new ionic energetic compounds. Most of the metal salts are highly sensitive primary explosives with quite high thermal stabilities for this type of highly energetic anion.